Motivational-emotional and cognitive factors of sports preparedness of young basketball players - Frolova, L.; Tymofeev, A.; Khomenko, I. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to establish the degree of influence of motivational-emotional and cognitive factors on the athletic preparedness of young basketball players, taking into account the exercise of the dominant and subdominant hands.